PHOTOCATALYTIC DEGRADATION Cr (VI) BY ZSM-5 IMPREGNATED TiO2 IN VARIOUS UV-IRRADIATION TIME - Faridah Faridah; Ana Hidayati Mukaromah; Ayu Rahmawati Sulistyaningtyas (Universitas Muhammadiyah Semarang, 2018)
Chromium is considered as one of the most common ubiquitous pollutants in aquatic environment. There were qualities standard about Chromium content in drinking water and fresh water. Oxidation of Chromium were Cr (II), Cr (III) and Cr (VI). Among these, Cr (VI) is considered as the most toxic form because it readily passes cellular membranes and then reduced to Cr (III). TiO2 as catalyst can activated and modified zeolites with active metal materials i.e ZSM-5 impregnated TiO2. Main objective of study was to determine decreased percentage of Cr (VI) in water by using ZSM-5 impregnated TiO2 based on UV irradiation time. This study was used Completely Randomized Design i.e length of UV irradiation. Result showed Cr (VI) content was decreasing with various length of UV irradiation in 15;30;45;60;75 minutes, respectively is 17.01; 17.99; 18.99; 28,73; 36, 20%. The highest percentage decrease of Cr (VI) ion content during 75 minute UV irradiation is 39,42%. Chromium (VI) content could be solved with zeolite ZSM-5 impregnated TiO2 by using photocatalytic method. In conclusion, the longer UV irradiation time caused higher of decreased percentage Cr (VI). Keywords: Chromium, Photocatalytic, Zeolite, Impregnated